'Flash-forwards' and suicidal ideation: A prospective investigation of mental imagery, entrapment and defeat in a cohort from the Hong Kong Mental Morbidity Survey. - Ng, R; Di Simplicio, M; McManus, F; Kennerley, H; Holmes, E (Elsevier, 2016)
‘Flash-forwards’ - mental images of suicide - have been reported in selected Caucasian samples. Perceptions of defeat and entrapment are considered to be associated with suicidal ideation. We aimed to investigate (1) the presence of suicidalflash-forwards in people with recent suicidal ideation versus those without such ideation in an Asian sample, and (2) associations between suicidal flash-forwards, and perceptions of entrapment accounting for suicidal ideation. Eighty two suicidal and 80 non-suicidal participants from the Hong Kong Mental Morbidity Survey completed questionnaires including suicidal ideation, presence of suicidalflash-forward images, defeat and entrapment, at baseline and seven weeks later. Suicidal‘flash-forwards’ were present only in suicidal cases. People with recent suicidal ideation and suicidal flash-forwards had more severe suicidal ideation than those withoutflash-forwards. Compared to those without suicidal ideation, people with recent suicidal ideation reported higher entrapment and defeat levels. Resolution of suicidal ideation over time was associated with fewer suicidalflash-forwards and reduced entrapment perceptions. At baseline and seven weeks, suicidal ideation was predicted by an interaction between suicidal flash-forwards presence and perceptions of entrapment. Mental imagery of suicide appears to be associated with suicidal ideation, and may represent a novel target in suicidal risk assessment and prevention.